Attitude Towards Teaching Physical Education Among Physical Health Education Undergraduates of Public Universities in Edo State, Nigeria - Obaze Agbonluae Osumah; Dorcas Edeme-Okonigene (Jurnal Ilmu Keolahragaan Undiksha, 2025)
This study investigated the attitude towards teaching physical education among physical health education undergraduates of public universities in Edo State, Nigeria.One research question and one hypothesis was analysed and tested respectively. The study adopted the descriptive research design. The total population comprised the 1040 (251 and 789) undergraduates in Human Kinetics and Health Education department of Ambrose Alli University Ekpoma and University of Benin, Benin City respectively. It covers only the 300 and 400 level undergraduates of the Human Kinetics and Health Education departments in Faculty of Education of Ambrose Alli University, Ekpoma and University of Benin, Benin City. The total sample size of 520 participants representing 50% of the population was drawn. The simple random sampling technique was employed to draw a sample size of 50% per university.The questionnaire used was adapted and re-titled:Students’ Physical Education Attitude Questionnaire (SPEAQ)”.The test-retest reliability procedure was adopted in determining the reliability of the instrumentwhich yielded an r-coefficient of 0.82.The mean ( ) and standard deviation (S.D) were used to analyse the research question while the hypothesis was tested using the t-test for two independent sample mean at 0.05 level of significance.The result showed that the attitude of Physical Education (PE) undergraduates in the public universities in Edo State towards teaching Physical Education is negative. This implies that Physical Education (PE) undergraduates hold unfavourable or restrictive predispositions about teaching their course of study. Furthermore, the attitude of PE students towards the teaching profession in the public universities in Edo State differed by sex with females holding more favourable disposition than their male counterparts.It was recommended thatPhysical and Health Education undergraduates should be exposed to education seminars and conferences that could help them to see the inherent values that could make them compete favourably with their colleagues in the world of work and also identify with the wealth of opportunities open to them within the teaching profession